1975
DOI: 10.1104/pp.56.6.836
|View full text |Cite
|
Sign up to set email alerts
|

Development and Intracellular Distribution of Enzymes of the Oxidative Pentose Phosphate Cycle in Radish Cotyledons

Abstract: Developmeental and compartmenitation studies were used to evaluate the relative roles of the oxidative pentose phosphate cycle, the Calvin cycle, and the glycoly-sis in cotvledons of radish (Raphanus sativus L.).Glucose-6-P dehydrogenase, 6-P-gluconate dehydrogenase, glucose-6-P isomerase, and the NAD-dependent glyceraldehyde-3-P dehydrogenase were present in high activity in ungerminated seeds, increased about 2-fold during germination in the dark, and were slightly enhanced by light. In contrast, NADP-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1978
1978
2000
2000

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…However, it has been possible by using anion-exchange chromatography to separate a11 other chloroplast/cytosol isoenzymes of sugar phosphate metabolism investigated to date, e.g. starch phosphorylase (Steup et al, 1980;Mateyka and Schnarrenberger, 1984), phosphoglucomutase (Mühlbach and Schnarrenberger, 1978), Glc-P isomerase (Schnarrenberger and Oeser, 1974), FBPase (Latzko et al, 19741, FBP aldolase (Kriiger and Schnarrenberger, 1983;Lebherz et al, 1984;Schnarrenberger and Kriiger, 1986), hexokinase (Schnarrenberger, 1990), G6PDH and 6PGDH (Schnarrenberger et al, 1973(Schnarrenberger et al, , 1975Simcox et al, 1977;Simcox and Dennis, 1978;Nishimura and Beevers, 19811, glyceraldehyde-3-P dehydrogenase (Miernyk and Dennis, 19821, 3-phosphoglycerate kinase (Miernyk and Dennis, 1982;Kopke-Secundo et al, 1990;Morrow and Bradbeer, 1990), triose-P isomerase (Kurzok and Feierabend, 1984), pyruvate kinase (Ireland et al, 1979), and enolase and phosphoglycerate mutase (Miernyk and Dennis, 1982;Plaxton, 1989). It is conceivable, yet we consider it highly unlikely, that isoenzymes for transaldolase, transketolase, Rib-5-P isomerase, and ribulose-5-P epimerase exist but are undetectable.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been possible by using anion-exchange chromatography to separate a11 other chloroplast/cytosol isoenzymes of sugar phosphate metabolism investigated to date, e.g. starch phosphorylase (Steup et al, 1980;Mateyka and Schnarrenberger, 1984), phosphoglucomutase (Mühlbach and Schnarrenberger, 1978), Glc-P isomerase (Schnarrenberger and Oeser, 1974), FBPase (Latzko et al, 19741, FBP aldolase (Kriiger and Schnarrenberger, 1983;Lebherz et al, 1984;Schnarrenberger and Kriiger, 1986), hexokinase (Schnarrenberger, 1990), G6PDH and 6PGDH (Schnarrenberger et al, 1973(Schnarrenberger et al, , 1975Simcox et al, 1977;Simcox and Dennis, 1978;Nishimura and Beevers, 19811, glyceraldehyde-3-P dehydrogenase (Miernyk and Dennis, 19821, 3-phosphoglycerate kinase (Miernyk and Dennis, 1982;Kopke-Secundo et al, 1990;Morrow and Bradbeer, 1990), triose-P isomerase (Kurzok and Feierabend, 1984), pyruvate kinase (Ireland et al, 1979), and enolase and phosphoglycerate mutase (Miernyk and Dennis, 1982;Plaxton, 1989). It is conceivable, yet we consider it highly unlikely, that isoenzymes for transaldolase, transketolase, Rib-5-P isomerase, and ribulose-5-P epimerase exist but are undetectable.…”
Section: Resultsmentioning
confidence: 99%
“…It was unequivocally shown that chloroplast/cytosol isoenzymes exist for G6PDH and 6PGDH both in green leaf cells (Schnarrenberger et al, 1973) and in nongreen tissues (Schnarrenberger et al, 1975;Simcox et al, 1977;Simcox and Dennis, 1978;Nishimura and Beevers, 1981). Cytosolic G6PDH has even been cloned from potato tuber (Graeve et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tables 1 and 3 show that there are clear differences between the populations studied. Gene frequencies (table 3) Distinct plastid (PGI-1) and cytosolic (PGI-2) forms of PGI, coded for at different loci, have been shown to exist in several species of angiosperm (Schnarrenberger and Oeser, 1974;Schnarrenberger et a!., 1975;Gottlieb and Weeden, 1979;1981;Weeden and Gottlieb, 1979;Jones, 1984). The most anodal PGI band was the same in all three species of Polygala, a lack of diversity typical of plastid isozymes (Gottlieb and Weeden, 1981).…”
Section: Differences Between Speciesmentioning
confidence: 99%
“…All individuals shared a single band in the most anodal zone (approximately 55 mm from the origin). This enzyme, designated PGI-1, was not well resolved on most gels, and, by analogy with the findings of studies on other plant species, was inferred to be the chloroplastic PGI (Schnarrenberger et al, 1975;Weeden & Gottlieb, 1980b;Gottlieb & Weeden, 1981;Gottlieb 1982). …”
Section: Cytosolic Pgi Phenotypesmentioning
confidence: 99%